Multicomponent reactions provide key molecules for secret communication - Andreas C. Boukis (Nature Portfolio, 2018)
Designing molecular keys and combining advanced encryption standard cryptography with molecular steganography is a secure way for encoding messages. Here, the authors use the Ugi four-component reaction of perfluorinated acids to create a library of 500,000 molecular keys for encryption and decryption.